Errors and Action Monitoring: Errare Humanum Est Sed Corrigere Possibile - Vidal, Franck; Burle, Boris; Hasbroucq, Thierry (Frontiers in Human Neuroscience, 2020)
It was recognized long ago by Seneca through his famous “errare humanum est.” that the human information processing system is intrinsically fallible. What is newer is the fact that, at least in sensorimotor information processing realized under time pressure, errors are largely dealt with by several (psycho)physiological-specific mechanisms: prevention, detection, inhibition, correction, and, if these mechanisms finally fail, strategic behavioral adjustments following errors. In this article, we review several datasets from laboratory experiments, showing that the human information processing system is well equipped not only to detect and correct errors when they occur but also to detect, inhibit, and correct them even before they fully develop. We argue that these (psycho)physiological mechanisms are important to consider when the brain works in everyday settings in order to render work systems more resilient to human errors and, thus, safer.